2020
DOI: 10.1038/s41598-020-62955-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional arrays of human pluripotent stem cell-derived cardiac microtissues

Abstract: To accelerate the cardiac drug discovery pipeline, we set out to develop a platform that would be capable of quantifying tissue-level functions such as contractile force and be amenable to standard multiwell-plate manipulations. We report a 96-well-based array of 3D human pluripotent stem cell (hPSC)-derived cardiac microtissues -termed Cardiac MicroRings (CaMiRi) -in custom 3D-printmolded multiwell plates capable of contractile force measurement. Within each well, two elastomeric microcantilevers are situated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Due to the single cell-based nature of the analyses, we were able to dissect bi-directional phenotypic changes in each specific cellular sub-type and evaluate them in the context of tissue level functional performance. While it is well established that non-myocytes are required to promote stable tissue formation 21,2629 , previous studies have described variable effects of different stromal or non-myocyte populations on cardiac function with limited details reported on phenotypic shifts in the co-cultured cells 21,30,31 . Therefore, we aimed to determine how age-specific CFs and ECs differentially affect cardiac tissue organization and calcium handling dynamics, resulting in transcriptional changes in the different heterotypic populations of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the single cell-based nature of the analyses, we were able to dissect bi-directional phenotypic changes in each specific cellular sub-type and evaluate them in the context of tissue level functional performance. While it is well established that non-myocytes are required to promote stable tissue formation 21,2629 , previous studies have described variable effects of different stromal or non-myocyte populations on cardiac function with limited details reported on phenotypic shifts in the co-cultured cells 21,30,31 . Therefore, we aimed to determine how age-specific CFs and ECs differentially affect cardiac tissue organization and calcium handling dynamics, resulting in transcriptional changes in the different heterotypic populations of cells.…”
Section: Discussionmentioning
confidence: 99%
“…This complex directionality has been accommodated by seeding the cells onto arrays of elastomeric microposts, with each cell forming attachments to multiple posts, and then monitoring the positions of the post tips (i.e., the point of cell attachment) relative to their bases. Studies conducted with hiPSC-CMs indicated that the cells typically formed attachments with 13-20 microposts/cell and generated a contractile force of ~15 nN/cell, with a peak contractile power of 29 fW [76].Contractile measurements have also been conducted in populations of hPSC-CMs suspended in fibrin and stretched between flexible pillars [77], and in collagen rings positioned around elastomeric microcantilevers [78]; subsequent assessments confirmed that the contractile forces increased and decreased in response to positive and negative inotropic factors, respectively.…”
Section: Confirmation Of Psc-cm Identity and Functional Characterizationmentioning
confidence: 99%
“…In both models, different cardiac cells, including ECs and CFs, which can be hPSC-derived or primary cultured cells, are combined with hPSC-derived CMs at a specific ratio. In the case of the EHT models, the composition of the hydrogel and the concentration of the ECM used are also important parameters to ensure tissue structure and functionality [ 87 ].…”
Section: Engineering 3d Cardiac Microtissues To Better Mimic the Hmentioning
confidence: 99%
“…The EHT models described in the literature are composed of hPSC-derived CMs alone [ 88 , 89 , 90 , 91 ] or in combination with primary fibroblast/stromal cells [ 92 , 93 , 94 ] and endothelial cells (HUVECs) [ 95 ] normally embedded in an hydrogel-based matrix that is then shaped according to a specific format. One of the models that has been described is the ring-shaped EHT, in which the mixture is pipetted into circular casting molds, where the tissue condenses, and is then placed around passive-flexible holders [ 87 , 92 , 96 ]. A different strategy relies on the development of elliptic shaped or strip-like cardiac tissues, which are anchored and stretched between two flexible pillars [ 89 , 90 , 93 , 95 , 97 , 98 ].…”
Section: Engineering 3d Cardiac Microtissues To Better Mimic the Hmentioning
confidence: 99%
See 1 more Smart Citation